2002
DOI: 10.1889/1.1830771
|View full text |Cite
|
Sign up to set email alerts
|

4.3: A Novel Synthesis of Y2O3: Eu Phosphor Using Carbon Dioxide and Ammonia for High Definition CRT and FED Applications

Abstract: Phosphor particles of regular shape and size have been synthesised by a new method. Depending on conditions the shape of the particles can be controlled and varied. The particles orient when deposited on screens and display greater luminance at low voltages than commercial and spherical phosphor samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The urea homogeneous precipitation method ,, was used to prepare spherical Y 2 O 3 :Ho 3+ hydroxycarbonate submicrometer phosphor precursor powders.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The urea homogeneous precipitation method ,, was used to prepare spherical Y 2 O 3 :Ho 3+ hydroxycarbonate submicrometer phosphor precursor powders.…”
Section: Methodsmentioning
confidence: 99%
“…The reason we are studying the properties of cubic Y 2 O 3 :M 3+ compounds is that we have developed a number of methods of homogeneously precipitating the phosphor precursors (to ensure atomic mixing) and controlling particle and crystallite sizes. [5][6][7][8][9][10] Furthermore, this phosphor lattice is very stable and we believe that because of the homogeneity of the dopant species, we can provide a good model for looking at interactions between evenly distributed activator ions. When M 3+ was Eu 3+ , the 632.8 nm (equivalent to a wavenumber of 15 803 cm -1 ) light had insufficient energy to directly promote a transition from the ground states to the excited states (i.e., the 5 D 0 state of Eu 3+ ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…x (where x ¼ 0.2-5 Â 10 À7 ) can be controlled [1][2][3][4][5][6][7][8][9][10][11]. We have reported their suitability as lowvoltage cathodoluminescent (CL) phosphors for FED applications for voltage regimes from 400 to 1500 V and shown their performance is comparable to commercial CRT powders [3].…”
Section: Introductionmentioning
confidence: 99%
“…As part of our continuing investigation into the control of phosphor particle size and morphology [1][2][3][4][5][6][7][8][9][10][11][12][13] we have found that not only particle size but also crystallite size within each particle is an important factor in phosphor performance. Spherical phosphor particles in the 200 nm to 400 nm diameter range containing crystallites in the size range 30 nm to 80 nm have been shown to manifest good CL properties [1,2,4,5,8,[10][11][12][13]. We report here a method for producing small particles of zinc gallate doped with manganese (Zn 1-x Mn x Ga 2 O 4 ).…”
Section: Introductionmentioning
confidence: 99%